High Tibial Osteotomy with a Modern Polyetheretherketone (PEEK) System: Mid-Term Results at a Mean of 6 Years Follow-Up - Keyt, Lucas K.; Hevesi, Mario; Levy, Bruce A.; Krych, Aaron J.; Camp, Christopher L.; Stuart, Michael J. (The Journal of Knee Surgery, 2020)
The purpose of this study was to determine patient-reported outcomes, hardware removal rates, as well as conversion to arthroplasty at mid-term follow-up following high tibial osteotomy (HTO) with a modern polyetheretherketone (PEEK) system. All PEEK system-based HTOs performed at a single institution between January 2010 and January 2016 with a minimum of 2 years follow-up were reviewed. Rates of postoperative complications, hardware removal and conversion to arthroplasty were calculated. Patient-reported outcomes including visual analog pain scale (VAS), Tegner activity scale, Lysholm, Knee Injury and Osteoarthritis Outcome Score (KOOS), and 36-Item Short Form Survey (SF-36) were obtained. Forty-seven HTOs in 43 patients (mean age: 37.6 ± 10.8 years; 30 M, 13 F) were followed for a mean of 6.0 ± 1.5 years. A total of four postoperative complications occurred in three patients, resulting in an overall complication rate of 6.4%. Hardware removal occurred in three patients at a mean of 0.73 ± 0.53 years after surgery, with overall survival free of hardware removal of 96% (95% confidence interval [CI]: 85–99) at 1 year, 94% (95% CI: 82–98) at 2 years, and 94% (95% CI: 82–98) at 8 years. Conversion to arthroplasty occurred in three patients at a mean of 3.2 ± 1.0 years after surgery, with mean survival of 100% (95% CI: 94–100) at 1 year, 100% (95% CI: 94–100) at 2 years, and 93% (95% CI: 81–98) at 8 years. VAS at rest improved, from 3.1 ± 2.5 preoperatively to 1.1 ± 1.6 postoperatively (p < 0.001). Patients remained active, with a mean Tegner activity scale of 4.4 ± 1.4 at final follow-up and satisfactory Lysholm, KOOS, and SF-36 scores. At mid-term follow-up, medial opening-wedge HTO using a modern PEEK-based system was found to be safe, efficacious, and durable, with satisfactory outcome scores and a low rate of conversion to arthroplasty. PEEK-based implants were found to have low hardware removal rates of 6% at 5 years, which compares favorably to historic metal fixation. This is a Level III study.
Keywords: high tibial osteotomy; polyetheretherketone; hardware removal rates; complication rate; KOOS; Tegner activity score; SF-36 score